Contribution of Saudi Arabia to regional and global publications on COVID-19-related research: A bibliometric and visualization analysis - Abdulrahman F. AlBloushi (Elsevier, 2022)
Background: At the global level and in Saudi Arabia, COVID-19 remains a major public health problem. The COVID-19 pandemic contributed substantially to a surge in publications on the novel coronavirus responsible for this pandemic. This research is intended to assess the increasing contribution of Saudi Arabia to the global research on COVID-19. Methods: A bibliometric analysis of all Saudi-affiliated publications on COVID-19 documented between December 2019 and October 2021 was conducted in October 2021 using the Web of Science advanced search builder. Results: A total of 175,615 global publications on COVID-19 were retrieved in the search. Among these, 9118 (5.2%) publications were from Arab nations. Among the Arab nations, Saudi Arabia (n = 3615) had the highest number of COVID-19 publications, followed by Egypt (n = 2053) and the United Arab Emirates (n = 1057), respectively. Globally, Saudi Arabia ranked 15th among the countries with the highest publication productivity, and the rank was 11th after standardization based on the population size and the gross domestic product. International collaborations were mainly with the researchers from Egypt, followed by the United States, India, Pakistan, and the United Kingdom. King Saud University was the most productive among all institutes in terms of COVID-19-related publications at both local and regional levels. Conclusion: Saudi Arabia is the leading Arabian nation and one of the top fifteen nations worldwide in terms of COVID-19 research output. Further efforts are warranted from the researchers based in Saudi Arabia in the direction of increasing the quality and the number of publications at the global level. This can be achieved by timely response, proper planning, understating the global research progress, and enhancing the knowledge exchange and collaboration with the other local and international institutes.